Surgical management of non-traumatic hypopharyngeal perforation with descending mediastinitis - Ivoslav Ivanov; Dimo Mitev (Folia Medica)
Perforation of the hypopharynx is an extremely rare condition of various etiologies. In even rarer cases, it can lead to mediastinitis, a serious complication with a high mortality rate of up to 35%. We present a case of a 52-year-old male patient with a purulent descending mediastinitis caused by a rare condition of rupture of the hypopharynx after the ingestion of solid food. Mediastinal gas and fluid as well as pleural empyema were observed on CT scan. The case is unique because of the cervical surgical approach used to treat it, as well as a number of techniques that appear to control the infection and treat the source of mediastinitis. The patient recovered completely 20 days postoperatively and was followed up clinically and by computed tomography without persistent symptoms or late complications.